The utilization of lime and plastic sack fiber for the stabilization of clay and their effect on CBR value - Enden Mina; Woelandari Fathonah; Rama Indera Kusuma; Ina Asha Nurjanah (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2021)
The soil of Kubang Laban Road at Terate Village, Kramatwatu-Serang district, can be classified as a clay soil type with a low bearing capacity with a field California Bearing Ratio (CBR) value of 2.16%. Therefore it is necessary to improve the soil, which is stabilization using added lime and plastic sack fiber. This study used variations of Plastic sacks fiber content 0%; 0.2%; 0.4%; 0.6% and 0.8% with the addition of 10% lime for each variation of the total dry weight of the soil. This study determines how adding plastic sack fiber and lime in the subgrade soil affects the CBR value and physical properties. The soil classification system used is based on the unified soil classification system (USCS). The results showed that the original soil was classified as OH type, organic clay with high plasticity. Thus, soil stabilization with plastic sack fiber and lime may reduce the IP and enhance the CBR. With 0.2 percent plastic sack fiber and 10% lime, the greatest CBR value was 41.78 percent. The optimum CBR value obtained meets the requirements for a road construction subgrade. Tanah di Jalan Kubang Laban Desa Terate Kecamatan Kramatwatu-Serang dapat tergolong jenis tanah lempung yang memiliki daya dukung rendah dengan nilai california bearing ratio (CBR) lapangan rendah yaitu 2.16%, sehingga perlu dilakukan perbaikan tanah. Salah satu cara perbaikan tanah adalah dengan penambahan kapur dan serat karung plastik. Penelitian ini bertujuan untuk mengetahui pengaruh penambahan serat karung plastik dan kapur pada tanah dasar terhadap nilai CBR dan sifat fisiknya. Penelitian menggunakan variasi kadar serat karung plastik 0%; 0,2%; 0,4%; 0,6% dan 0,8% dengan penambahan kapur 10% untuk setiap variasi berat kering total tanah. Sistem klasifikasi tanah yang digunakan didasarkan pada sistem klasifikasi Unified Soil Classification System (USCS). Hasil penelitian menunjukkan bahwa tanah asli tergolong jenis OH, lempung organik dengan plastisitas tinggi. Stabilisasi tanah dengan menggunakan karung plastik fiber dan kapur dapat menurunkan nilai indeks plastisitas (IP) dan meningkatkan nilai CBR. Berdasarkan hasil pengujian CBR, nilai CBR tertinggi diperoleh pada variasi serat karung plastik 0,2% dengan kapur 10% sebesar 41,78%. Nilai CBR optimum yang diperoleh memenuhi persyaratan untuk tanah dasar konstruksi jalan.